WRONGDOERS AND THEIR CONSCIENCE IN SHORT STORIES BY O. HENRY = NGƯỜI PHẠM TỘI VÀ LƯƠNG TÂM CỦA HỌ TRONG CÁC TRUYỆN NGẮN CỦA O. HENRY - Vũ, Tuyết Linh (2021)
O. Henry is a well-known master of short stories. With his unique writing style along with surprising endings, his masterpieces such as “The Gift of the Magi” and “The Last Leaf” have attracted many worldwide readers. Furthermore, readers have a great feeling of O. Henry’s short stories because of different types of characters. He wrote not only about good samaritans but also wrongdoers. However, in most of his stories, this author would like to find out the good conscience in his figures because according to him everyone possesses a good human nature. For this reason, the graduation paper is conducted in order to explore wrongdoers and their conscience in more detail among famous short stories related to this topic. The study contains three parts. The first one is Introduction which includes Rationale, Method of working and Scope of the study. The second part – Development is divided into three chapters. Chapter one is Literature review which is divided into three small sections: literature theories, historical background and American literature in the late 19th and early 20th century. Chapter two comprises more details about O. Henry’s life, his literary career as well as summaries of some of his selected short stories. In chapter three, there is a detailed analysis of wrongdoers and their conscience. The last part, Conclusion, is composed of the summary and limitations of the graduation paper. Also, suggestions for further research are mentioned in this chapter.